2022
DOI: 10.3390/cells11203291
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Universe of Eph Receptor and Ephrin Ligand Transcripts in Epithelial and Fiber Cells of the Eye Lens

Abstract: The eye lens is a transparent, ellipsoid organ in the anterior chamber of the eye that is required for fine focusing of light onto the retina to transmit a clear image. Cataracts, defined as any opacity in the lens, remains the leading cause of blindness in the world. Recent studies in humans and mice indicate that Eph–ephrin bidirectional signaling is important for maintaining lens transparency. Specifically, mutations and polymorphisms in the EphA2 receptor and the ephrin-A5 ligand have been linked to congen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 51 publications
2
8
0
Order By: Relevance
“…Using traditional, qualitative PCR, 12 of 14 Ephs and 8 of 8 ephrins were previously detected in the lenses of young adult wild-type, EphA2 –/– , and Efna5 –/– mice ( 27 ). Unfortunately, the large number of genes expressed did not sufficiently narrow down targets of interest to pursue.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using traditional, qualitative PCR, 12 of 14 Ephs and 8 of 8 ephrins were previously detected in the lenses of young adult wild-type, EphA2 –/– , and Efna5 –/– mice ( 27 ). Unfortunately, the large number of genes expressed did not sufficiently narrow down targets of interest to pursue.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the promiscuous nature of Eph-ephrin binding, the number of permutations of receptor-ligand combinations presents a formidable barrier to identify binding partners of interest ( 10 , 25 , 26 ). In the endeavor to narrow targets, a concerted effort to identify the Ephs and ephrins that are present in the mouse lens found that 12 of 14 known Ephs and 8 of 8 known ephrins were expressed ( 27 ). Here, the next step of this search is presented, in which these previously observed Ephs and ephrins are investigated in a quantitative manner.…”
Section: Introductionmentioning
confidence: 99%
“…In different species, the disruption of Eph-ephrin signaling was found to be cataractogenesis [23][24][25] . Vu and Cheng [26] extracted and sequenced Eph receptor and ephrin ligand transcripts in adult mice and discovered that practically all Ephs and ephrins were expressed in the adult mouse lens. The spatiotemporal specificity of the expression of other receptor-ligand pairs and their role in the lens, and whether they are affected in the ephrin-A5 mutant lens remain to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…For example, congenital cataracts, a form of cataract in children, are generally characterized by defects in the structure or function of lens proteins and/or their coding genes, which can lead to lens opacity [12] . Utilizing cell biology research methods, we can investigate the pathogenic genes, the abnormalities in the structure of the encoded proteins, and their consequences [15,26] . For instance, changes in isoelectric point or local hydrophobicity/hydrophilicity can cause abnormal aggregation of crystallin, leading to a loss of solubility of high concentrations of intracellular proteins and resulting in lens opacity [12] .…”
Section: Discussionmentioning
confidence: 99%
“…The coordinated elongation and migration of cohorts of lens fiber cells plays an key role in the development of lens sutures [49] . EPHA2-null lenses have displayed the sutural defects and disturbances in the surface patterning of individual fiber cells, implying that EPHA2 has a role in the directed migration of lens fiber cells [50] . Murugan and Cheng [51] reported that the wild-type EPHA2 promoted the migration of mouse lens epithelial αTN4-1 cells in the absence of ligand stimulation, and that the variants in SAM domain diminished this activity.…”
Section: Epha2/pr957p Variant Promoted Cell Migration In Sramentioning
confidence: 99%